PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI KECAMATAN SERENGAN KOTA SURAKARTA - Partono, Joko (JI@P, 2016)
Sub-district of Serengan Office is one of the office located in Surakarta UrbanArea performs public services is demanded to work prfessionally and should beable to respond the public aspiration and the environmental changes. In order toincrease the civil servants performance, it can be done by performingprofessional leadership style, creating good work environment, and a high anddirected work motivation. This research aimed to analyse partially as well assimultaneously the influence of leadership style, work motivation, and of workenvironment toward civil servantsâ work performance. The research wasconducted in Serengan Sub-district Surakarta Urban Government. Quantitativeapproach was used in this study. The population of civil servants working in theSub-district of Serengan as much as 83 was surveyed. Statistical analysisemployed regression, including t test, F test, and finding the coefficient ofdetermination. Research result showed that: (1) There was a positive andsignificance influence of leadership style toward the work performance; (2) Therewas a positive and significant influence of work motivation upon the workperformance; (3) There was a positive and significance influence of workenvironment upon the work performance; and (4) There is simultant influence ofthose three indendent variables upon the work performance. Based on thefinding it can be concluded that the higher the influence of the degree ofleadership style, work motivation, and work environment, the more likely thehigher the degree of work performance, partially as well as simultaneously.Key words: Leadership style, work motivation, work environment, work performance.